Levels and Factors of Mathematics Anxiety in Prospective Teacher Students - Prafianti, Rayinda Aseti; Febriyanti, Rahma; Anjarsari, Elly; Silvia, Ifroha Anita (Discovery, 2025)
Mathematics anxiety is one of the inhibiting factors in learning which can interfere with the performance of cognitive functions such as concentration, remembering, concept formation and problem solving. Therefore, mathematics anxiety needs to be minimized by examining more deeply the levels and factors of mathematics anxiety. The purpose of this research is to explain the level and factors of mathematics anxiety in prospective teacher students at Mathematics Education Department Universitas Islam Lamongan. Instrument used is questionnaire of mathematics anxiety. The number of subject is 24 students. Based on the questionnaire of mathematics anxiety level, it was found there are three levels of anxiety experinced by the students, namely heavy, medium, and low mathematics anxiety. Heavy mathematics anxiety is experienced by 7 students, medium mathematics anxiety is experienced by 10 students, and low mathematics anxiety is experienced by 7. The factors that affect the level of mathematics anxiety are don't believe himself about his abilities, unpleasant experience in the past, unable to understand the mathematics material well, and pressure from parents to become a mathematics teacher. It can be concluded that prospective teacher students in mathematics education department Universitas Islam Lamongan experience the medium to heavy anxiety level.